Gestión del talento humano y desempeño laboral en el área de recursos humanos de Electro Oriente, Iquitos 2023 - Tello Hidalgo, Claudio Geronimo (2024)
In 2023, a study was conducted in the Human Resources department of Electro Oriente, Iquitos, with the purpose of investigating the relationship between human talent management and job performance. The methodology used was of a descriptive correlational nature with a quantitative approach, and the research design was non-experimental, meaning that variables were not manipulated; rather, phenomena were observed in their natural state. The most significant result of this research revealed a very strong positive correlation, as reflected by a Pearson correlation coefficient of 0.926, with a bilateral significance value of 0.000. Additionally, the calculated p-value was less than 0.05, leading to the confirmation of the hypothesis that a significant relationship exists between human talent management and job performance in the Human Resources department of Electro Oriente, Iquitos in 2023. According to the Pearson correlation coefficient and the established decision criteria, it can be concluded that there is a significant relationship between human talent management and job performance in this specific context.